Abstract 209: Incidence and outcome of perforations during medium‐vessel occlusion compared to large‐vessel occlusion thrombectomy - Marios Psychogios (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Vessel perforation during thrombectomy is a severe complication and is hypothesized to be more frequent during MeVO thrombectomy. The aim of this study was to compare the incidence and outcome of patients with perforation during MeVO and LVO thrombectomy and to report on the procedural steps that led to perforation. Methods In this multicenter retrospective cohort study, data of consecutive patients with vessel perforation during thrombectomy between January 01, 2015 and September 30, 2022 were collected. The primary outcomes were independent functional outcome (i.e. modified Rankin Scale 0‐2) and all‐cause mortality at 90 days. Binomial test, chi‐squared test and t‐test for unpaired samples were used for statistical analysis. Results During 25,769 thrombectomies (5,124 MeVO, 20,645 LVO) in 25 stroke centers, perforation occurred in 335 patients (1.3%; mean age 72 years, 62% female). Perforation occurred more often in MeVO thrombectomy (2.4%) than in LVO thrombectomy (1.0%, p < 0.001). More MeVO than LVO patients with perforation achieved functional independence at three months (25.7% vs 10.9%; p=0.001). All‐cause mortality did not differ between groups (overall 51.6%). Navigation beyond the occlusion and retraction of stent‐retriever/aspiration catheter were the two most common procedural steps that led to perforation. Conclusion In our cohort, perforation was approximately twice as frequent in MeVO than in LVO thrombectomy. Efforts to optimize the procedure may focus on navigation beyond the occlusion site and retraction of stent‐retriever/aspiration catheter. Further research is necessary in order to identify thrombectomy candidates at high risk of intraprocedural perforation and to provide data on the effectiveness of endovascular countermeasures.